Novel Medical Therapies for Pituitary Tumors - Theodoropoulou, M. (2010)
Despite considerable progress, there is still no medical treatment available for some kinds of pituitary tumors, in particular hormone inactive adenomas and corticotroph pituitary tumors. Surgical removal or at least debulking of the tumor is the only option to treat these kinds of tumors apart from rarely applied radiotherapy. Moreover, treatment resistance is present in a considerable proportion of patients bearing pituitary tumors, for which medical treatment regimens are already available (prolactinomas, somatotroph adenomas). Thus, novel or improved medical treatment strategies would be desirable. Here, we summarize preclinical and clinical findings about the hormone and growth-suppressive action of various drugs, which will probably lead to novel future medical treatment concepts for pituitary tumors.